Modal Characteristics of Composite Beams with Single Delamination- A Simple Analytical Technique - Keyvan Torabi; Mostafa Shariati-Nia; Mohammad Heidari-Rarani (Mechanics of Advanced Composite Structures)
In the present research, the effects of delamination size and location on vibration characteristics of laminated composite beams are investigated both analytically and numerically. In the analytical method, the delaminated beam is modeled as four interconnected Euler–Bernoulli beams and the constrained and free mode models are both simulated. The differential stretching and the bending-extension coupling are considered in the formulation. Analytical expressions for displacement functions are presented in a simple form based on the basic standard trigonometric and hyperbolic functions. This new technique considerably simplifies the calculations regardless of the number of delaminations. In finite element method, delaminated composite beams are modeled in commercial finite element software, ABAQUS, and natural frequencies and mode shapes are extracted from the modal analysis. Analytical results are compared with finite element ones and available experiments in the literature. Finally, the generated database for different sizes and locations of delamination can be used to detect the existence of delamination in laminated composite beams and thento specify the size and location of delamination.